CircFOXO3 upregulation mediates the radioresistance of glioblastoma by affecting cellular metabolome - Xu, Hao; Xing, Jin; Cheng, Lilin; Wang, Zhihan; Zhao, Liang; Ren, Li; Zhang, Shuai (Frontiers in Pharmacology, 2024)
Radioresistance remains a significant challenge in the treatment of glioblastoma multiforme (GBM), the most prevalent and lethal brain cancer in adults. Metabolic alterations are known to contribute to radioresistance through various mechanisms, including the activation of antioxidant responses to counteract reactive oxygen species and the promotion of DNA repair. In this study, we observed significant upregulation of circular RNA forkhead box O3 (circFOXO3) in glioma cells upon exposure to radiation and in recurrent GBM tissues. Knockdown of circFOXO3 was found to increase the radiosensitivity of glioma cells both in vitro and in vivo. Conversely, overexpression of circFOXO3 attenuated radiosensitivity in glioma cells. Metabolomic analysis revealed substantial alterations in the metabolomic profiles between the circFOXO3-overexpressing and control groups post-irradiation, particularly with respect to lipids and lipid-like molecules, organic acids and derivatives, and organoheterocyclic compounds. Furthermore, the suppression of circFOXO3 expression increased the levels of the proapoptotic proteins Caspase 7 and Bax while decreasing Bcl-2 levels after radiotherapy. Our findings highlight the crucial role of circFOXO3 in promoting tumor radioresistance through metabolic modulation, underscoring its potential as a diagnostic and therapeutic target for GBM.